2011
DOI: 10.2166/wst.2011.566
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of magnetic separation of magnetic nanoparticle for forward osmosis

Abstract: It was recently reported that a UK company has developed a naturally non-toxic magnetoferritin to act as a draw solute for drawing water in forward osmosis process. The gist of this technology is the utilization of the magnetic nanoparticle and high-gradient magnetic separation for draw solute separation and reuse. However, any demonstration on this technology has not been reported yet. In this study, a feasibility test of magnetic separation using magnetic nanoparticle was therefore performed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…between nanoparticle size and osmolality using PAA-MNPs. However, Kim et al [56] found that particles smaller than 11 nm were difficult to separate from solution even with the application of a strong magnetic field, while the removal of particles larger than about 20 nm from the magnetic separator column was problematic. Additionally, the larger the mass percentage of coating material on a Fe 3 O 4 core, the lower the saturated magnetization value on a per gram of particle basis.…”
Section: Particle Sizementioning
confidence: 99%
“…between nanoparticle size and osmolality using PAA-MNPs. However, Kim et al [56] found that particles smaller than 11 nm were difficult to separate from solution even with the application of a strong magnetic field, while the removal of particles larger than about 20 nm from the magnetic separator column was problematic. Additionally, the larger the mass percentage of coating material on a Fe 3 O 4 core, the lower the saturated magnetization value on a per gram of particle basis.…”
Section: Particle Sizementioning
confidence: 99%
“…12,13 Another challenge is the easy agglomeration of the NPs, which leads to poor re-suspension and reduced performance with repeated use.…”
Section: -10mentioning
confidence: 99%
“…Furthermore, for the small-sized CoFe 2 O 4 particles, an agglomeration would occur during their magnetic separation, and the resulting aggregates are difficult to re-disperse even with intense ultrasonication. 13,46 This explains the much poorer re-suspension of CoFe 2 O 4 than the larger-sized yet welldispersed CoFe 2 O 4 -CNS (Fig. 6 Inset).…”
mentioning
confidence: 96%
“…Transition‐metal‐based magnetic nano‐scale particles have drawn the attention of researchers because of their particular properties such as their high surface area, low toxicity, excellent chemical stability, and biodegradability. As a result of their magnetic properties and biodegradability, they are used in drug delivery, magnetic resonance cell imaging, magnetic hyperthermia, dye adsorption, magnetic separation, wastewater treatment, and heavy‐metal removal . Such magnetic nanoparticles are also applicable as catalysts in industry .…”
Section: Introductionmentioning
confidence: 99%